Effect of climate and ripening on sour cherry Maraska and Oblačinska bioactive properties - Repajić, Maja (Array, 2018)
The aim of this study was to examine the influence of climate conditions and ripening on total phenols (TP), total monomeric anthocyanins (TAC) and antioxidant capacity (AC) of Maraska and Oblačinska sour cherries. For that reason, TP using Folin-Ciocalteau reagent, TAC by pH-differential method and AC via DPPH method were determined in Maraska and Oblačinska sour cherry samples harvested in Zadar and Osijek area in 2014 at three maturity stages. Despite that statistical analysis showed significant differences in TP and AC between cultivars and growing locations, obtained results revealed considerable functional properties of both cultivars. Still, Maraska achieved higher TP, TAC and AC values compared to Oblačinska. Furthermore, Mediterranean climate conditions positively affected on bioactive compounds accumulation in both cultivars, where generally the highest contents of examined bioactive compounds were accomplished at the latest harvest date.